Anthelmintic resistance of Haemonchus contortus from sheep flocks in Brazil: concordance of in vivo and in vitro (RESISTA-Test©) methods - Gainza, Yousmel Alemán [UNESP]; Santos, Isabella Barbosa Dos [UNESP]; Figueiredo, Amanda [UNESP]; Santos, Leonardo Aparecido Lima Dos; Esteves, Sérgio Novita; Barioni-Junior, Waldomiro; Minho, Alessandro Pelegrine; Chagas, Ana Carolina de Souza (FapUNIFESP (SciELO), 2021)
This study evaluated the resistance status of Haemonchus contortus from sheep flocks in the state of São Paulo, Brazil, through comparison between the fecal egg count reduction test (FECRT) and the larval development test (LDT). For the FECRT, 35 sheep were selected in each of five flocks and divided into groups treated with: benzimidazole, levamisole, ivermectin, monepantel and control. Feces were collected for EPG and fecal cultures. The LDT was performed using thiabendazole (TBZ), levamisole (LEV), ivermectin aglycone (IVM-A) and Zolvix (ZLV). Resistance to all drugs was detected using FECRT in 100% of the flocks, except in relation to ZLV (40% resistant and 20% suspected of resistance). LDT indicated resistance to TBZ and IVM-A in all flocks, to LEV in 80% of flocks and to ZLV in 10%. Total agreement was obtained between the two tests for TBZ and IVM (k = 1.0), while for LEV (k = 0.8) and ZLV (k = 0.9), substantial and almost perfect agreement were obtained, respectively. The concordance between the tests was significant, thus showing that it is possible to use the outcome of the LDT to predict the FECRT, and hence validating the former as a fast diagnostic test for use by sheep farmers in Brazil.